2004
DOI: 10.1090/s0077-1554-04-00147-5
|View full text |Cite
|
Sign up to set email alerts
|

Stable pencils of hyperbolic polynomials and the Cauchy problem for hyperbolic equations with a small parameter at the highest derivatives

Abstract: Abstract. We study pencils of hyperbolic polynomials of the form R (τ, ξ, where P j (τ, ξ) is a real homogeneous polynomials of degree m − j resolved with respect to the highest power of τ and P j (1, 0) = 1; the numbers γ 0 , . . . , γ N are positive. In the first part of the paper we find necessary and close to sufficient conditions of stability of the polynomial R(τ, ξ) (i.e., the condition that its roots τ j (ξ) lie in the open upper half-plane of the complex plane). This problem is closely related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…is positive on the cone K 0,3;1,4 for arbitrary [6]. In the first case, we obtain inequality (23), and in the second case, we arrive at (24).…”
Section: Sufficient Weight Conditions For the Stability Of A Polynomimentioning
confidence: 54%
“…is positive on the cone K 0,3;1,4 for arbitrary [6]. In the first case, we obtain inequality (23), and in the second case, we arrive at (24).…”
Section: Sufficient Weight Conditions For the Stability Of A Polynomimentioning
confidence: 54%
“…The size of these systems depends on the number of moments and dimension of the space. Some examples of these systems and their stability has been analysed in [VR03].…”
Section: Applicationsmentioning
confidence: 99%
“…In [VR04] it was shown that P M +1 (τ, ξ) ≡ 0, γ M P M (τ, ξ) = M!τ for some γ M > 0, and γ M −1 P M −1 (τ, ξ) = M! M +1 k=2 1 k−1 τ 2 − M!|ξ| 2 for some γ M −1 > 0.…”
Section: Fokker-planck Equationmentioning
confidence: 99%
“…Clearly, in this situation it is hard to find the roots explicitly, and, therefore, we need some procedure of determining what are the general properties of the characteristics roots, and how to derive the time decay rate from these properties. Thus, in [Rad03] and [VR04] it is discussed when such polynomials are stable. In this case, the analysis of this paper will guarantee the decay rate, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, making the decomposition in the space of velocities into the Hermite basis, and writing equations for the space-time coefficients produces a hyperbolic system for infinitely many coefficients (see e.g. [VR03], [VR04], [ZR04], and Section 8.5). The Galerkin approximation of this system leads to a family of systems with sizes increasing to infinity.…”
mentioning
confidence: 99%